A comparative study on the effects of a VR and PC visual novel game on vocabulary learning. Issue 3 (4th March 2023) - Lai, Kuo-Wei Kyle; Chen, Hao-Jan Howard
Abstract: Research on vocabulary acquisition in digital game-based learning has been increasing over the years, with advancements in technology giving rise to numerous learning alternatives in second language acquisition. As virtual reality gaming offers new opportunities to explore its effectiveness in language learning, it is thus important to investigate the benefits of virtual reality gaming on English vocabulary learning, as well as the potential in incorporating virtual reality to teaching practices in the classroom. Therefore, this study aims to investigate the effects of virtual reality (VR) and personal computer (PC) gaming on language learners' vocabulary learning, as well as their affective perception. Thirty Grade 12 high school students participated in this study and were randomly assigned to either the VR or PC group. The VR group played a Sci-fi VR visual novel game, Angels and Demigods, using the Oculus Go whereas the PC group played the same game in the PC version without the VR elements. The gaming session lasted for fifty minutes for both groups. A vocabulary translation and recognition pretest, posttest and delayed posttest were adopted to compare their performance, along with a questionnaire to probe into their perception towards their respective treatment. The results revealed that both the VR group and the PC group were able to gain vocabulary knowledge in both the translation and recognition tests. In comparison, the VR group demonstrated a significantly higher mean score than the PC group in the vocabulary translation delayed posttest. The questionnaire showed that learners in both groups enjoyed playing the visual novel game and were willing to adopt it as a tool for learning vocabulary.